2003
DOI: 10.1161/01.cir.0000085066.05180.40
|View full text |Cite
|
Sign up to set email alerts
|

Cisapride-Induced Transmural Dispersion of Repolarization and Torsade de Pointes in the Canine Left Ventricular Wedge Preparation During Epicardial Stimulation

Abstract: Background-Cisapride, a gastrointestinal prokinetic agent, was recently withdrawn from the market because of its propensity to induce torsade de pointes (TdP) arrhythmias. The present study examines the electrophysiological actions of cisapride in the isolated arterially perfused canine left ventricular wedge preparation. Methods and Results-Transmembrane action potentials from epicardial and M regions and a pseudo-ECG were simultaneously recorded. Cisapride (0.1 to 5 mol/L) was added to the coronary perfusate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 27 publications
8
69
0
Order By: Relevance
“…The available data support the hypothesis that TDR, rather than QT prolongation, underlies the principal substrate for the development of TdP (9,11,27,46,54). Our working hypothesis for the development of long QT syndrome-related TdP presumes the presence of electrical heterogeneity in the form of TDR under baseline conditions and the amplification of TDR by agents that reduce net repolarizing current via a reduction in I Kr or I Ks or augmentation of I Ca or late I Na (Fig.…”
Section: Long Qt Syndromesupporting
confidence: 72%
“…The available data support the hypothesis that TDR, rather than QT prolongation, underlies the principal substrate for the development of TdP (9,11,27,46,54). Our working hypothesis for the development of long QT syndrome-related TdP presumes the presence of electrical heterogeneity in the form of TDR under baseline conditions and the amplification of TDR by agents that reduce net repolarizing current via a reduction in I Kr or I Ks or augmentation of I Ca or late I Na (Fig.…”
Section: Long Qt Syndromesupporting
confidence: 72%
“…Epicardial pacing involves a non-physiological activation sequence in which the vector of the transmural propagation is reversed, resulting in delayed endocardial depolarization and earlier epicardial depolarization. 24 Experimental studies have shown that epicardial-endocardial conduction time is significantly longer than endocardial-epicardial conduction time, due to a zone of myocardial wall between the deep subendocardium and mid-myocardial layers. 25,26 The resulting increased dispersion of repolarization prolongs QT The proarrhythmic effect of cardiac resynchronization therapy: An issue that should be borne in mind 309.e5…”
Section: Discussionmentioning
confidence: 99%
“…4 Diego et al demonstrated that the risk for TdP induction was related to the increase in TDR, rather than in the QT interval. 7 Scroll wave re-entry is the active source of excitation that sustains ventricular tachyarrhythmias. However, the role of TDR during scroll wave re-entry is not well understood.…”
Section: Tdr Determines Scroll Wave Behaviormentioning
confidence: 99%